The psychometric characteristics of the Kessler Psychological Distress Scale (K6) in help-seeking youth: What do you miss when using it as an outcome measure?. (November 2021) - Cotton, S.M.; Menssink, J.; Filia, K.; Rickwood, D.; Hickie, I.B.; Hamilton, M.; Hetrick, S.; Parker, A.; Herrman, H.; McGorry, P.D.; Gao, C.
Highlights: Psychological distress is a complex multidimensional phenomenon. Young people presenting to primary mental health services have higher levels of psychological distress. This is the first study to examine the psychometric properties of the Kessler Psychological Distress Scale 6 (K6) in young people presenting to mental health services. Positive indicators supporting the use of the K6 for mental health issues in young people included good internal consistency and concurrent validity with other brief measures of depression and anxiety. The K6 is a good screener for young people presenting in primary care, but may not be a good outcome measure due to issues with dimensionality, measurement non-invariance for sex and age groups, and it being less sensitive to changes compared to the PHQ-9 and GAD-7. Abstract: This is the first study to describe psychometric properties of the Kessler Psychological Distress Scale (K6) in a large cohort of help-seeking young people presenting to primary mental health care services. The aim was to determine whether the K6 was appropriate for monitoring outcomes in such settings. 1067 young people were recruited from Australian headspace services. We examined dimensionality of the K6, measurement invariance, and how the K6 correlated with the the Patient Health Questionnaire–9 (PHQ-9)and the Generalised Anxiety Disorder–7 Scale (GAD-7). Standardised Response Mean (SRM) and Cohen's d effect size (ES) were used to examine 3-month stability of the K6. The best-fitting model was a two-factor model: (i) nervous and restlessness; and (ii) hopeless, worthless, depressed and effort. Measurement non-invariance was observed for sex and age groups. K6 strongly correlated with the PHQ-9 and GAD-7. The K6 was less sensitive to change compared to these other two measures. There was some support for the K6 being a screener for young people presenting to primary care; however, there issues arise with its use as an outcome measure. These issues include measurement non-invariance, concern about the dimensionality and focus of items, and its sensitivity to change.